Optimization of the process of solid radwaste management at the ”Shelter” object transformation to the ecologically safety system - Batiy, V.G.; Stojanov, A.I. (Вопросы атомной науки и техники, 2007)
Methodological approach of optimization of schemes of solid radwaste management of the ”Shelter” object and ChNPP industrial site during transformation to the ecologically safe system was developed. Розроблена методика оптимізації схем звернення і технологій поводження з твердими радіоактивними відходами об'єкту "Укриття" і проммайданчика ЧАЕС в процесі їх перетворення об'єкту "Укриття" в екологічно безпечну систему. Разработана методика оптимизации схем обращения и технологий обращения с твердыми радиоактивными отходами объекта "Укрытие" и промплощадки ЧАЭС в процессе их преобразования объекта "Укрытие" в экологически безопасную систему.